San Fernando Hospital, Trinidad, The West Indies - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2009)
Exterior side view of the four-storeyed San Fernando Hospital depicting its driveway, plants and brilliant blue sky. Building is adjoined with 4 sections. Postcard number K6265.
Colour: Green, Red, Orange, Blue, White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Hospitals--Trinidad and Tobago; Health facilities--Trinidad and Tobago; Plants--Trinidad and Tobago; Shrubs--Trinidad and Tobago; [1975]; Architecture--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--San Fernando